Perancangan Sistem Informasi Administrasi Pembayaran Spp Pada Mts Nu 06 Sunan Abinawa Pegandon Kendal - Taufik hidayat; Atik Dina Nasikhah; Edi Hariyanto (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2023)
The web-based SPP payment administration information system at Mts Nu 06 Sunan Abinawa is an information system that manages financial administration such as managing SPP payment transactions. This web-based SPP payment information system was built using the programming language PHP (Hypertext Processor) and MYSQL as the database. The methodology used in the development of this system uses the Prototype model method. Due to the activity of paying tuition fees at Mts Nu 06 Sunan Abinawa it is still done manually, the recording process still uses ledgers when students make tuition payments causing the payment process to take a long time, the risk of losing data, the level of supervision is relatively low and there are difficulties in accessing data when preparing financial reports